Biological abnormalities of peripheral A(2A) receptors in a large representation of polyglutamine disorders and Huntington's disease stages - Varani, K; Bachoud-Lévi, A-C; Mariotti, C; Tarditi, A; Abbracchio, M P; Gasperi, V; Borea, P A; Dolbeau, G; Gellera, C; Solari, A; Rosser, A; Naji, J; et al. (Neurobiology of disease, 2007)
Huntington's disease is one of a group of hereditary neurodegenerative diseases characterized by a glutamine expansion (polyQ) in proteins which are expressed in various cell populations. In agreement with this widespread distribution, we have previously shown that A(2A) receptor signaling is affected in mouse brain as well as in peripheral blood cells from a small cohort of HD patients. Here we analyzed a total of 252 subjects, including 126 HD gene-positive individuals, from different clinical sites. Consistent with our previous data we show that A(2A) receptor B(max) values are robustly increased at all HD stages as well as in 32 pre-symptomatic subjects. We report that the same abnormality is present also in other polyQ but not in non-polyQ inherited neurological disorders. Finally, we demonstrate that the same peripheral cells exhibit an altered membrane fluidity, a finding that may explain the observed change in receptor density. We argue that the observed alteration in lymphocytes reflects the presence of the mutant protein, and we suggest that the measure of the A(2A) receptor binding activity might be of potential interest for a peripheral assessment of chemicals capable of interfering with the immediate toxic effects of the mutation.